Barriers: Music that crosses boundaries - Pikichian, Hripsime (History and Culture, 2025)
The tangible and intangible boundaries set by nature or humans are, from the beginning, dividing lines between eras, worlds, states, and cultures. Although these boundaries may seem unbreakable or exceedingly fragile, people sometimes seek to cross, remove, or, conversely, reinforce these barriers, directly or indirectly, when necessary.Occasionally, despite obstacles and under the influence of supreme forces known only to itself, music traverses both visible and invisible boundaries, re-establishing a sense of equilibrium and eternity. Reflecting on this, the figure of Orpheus [Kun, 2021, 301-306] comes to mind-a mythical musician whose lyre enchanted nature and even commanded therealm of Hades, ruler of souls of the dead. In this article, we will attempt, through a combination of scholarly literature, archival materials, and facts and oral histories gathered during field research, to explore the interrelations betweenboundaries, musicians, and music. This exploration will consider examples of peaceful coexistence as well as conflict situations. Thus, through four real stories, we will present different temporal, socio-cultural, and political perceptions and realities of the concept of boundaries. We will also explore the "right to break" boundaries earned by renowned musicians and their music, which, in the perceptions of various social groups, transcended religious, political, and social divisions and conflicts.